Urgensi Pembaharuan Asas-Asas Hukum Pada Undang-Undang No 37 Tahun 2004 Berdasarkan Teori Keadilan Distributif - Kautsar, Izzy Al; Muhammad, Danang Wahyu (Jurnal Panorama Hukum, 2020)
In Law Number 37 of 2004 there are many legal vacancies, due to the lack of existing legal principles causing injustice for the parties. The legal vacuum exists because there are many legal principles that are not heeded in the drafting of the Law, so that the justice of the parties is not guaranteed.. This research aims to find the principles that should exist in the Bankruptcy Law in order to be able to guarantee the continuity of perfect law and justice for the parties. This normative research used secondary data consisting of primary, secondary, and tertiary legal materials. It is found that the addition of legal principles is indispensable in order to maximize the presence of the bankruptcy law in Indonesia, the principle that needs to be added to the bankruptcy law is the principle which has an element of justice that is distributive justice.